Complete neurological recovery from fat embolism syndrome in sickle cell disease after sequential red cell exchange transfusion and therapeutic plasma exchange. (December 2021) - Tsitsikas, Dimitris A.; Mihalca, Diana; Bello-Sanyaolu, Oloruntoyin; Amposah, Rhoda; Olasoji, Susan; Orebayo, Funmilayo; Tham, Lawrence; Rowe, Susan
Abstract: Fat embolism syndrome in sickle cell disease is associated with great mortality, while more than half of survivors suffer severe neurological sequelae. Release of fat droplets leads to obstruction of the microcirculation as well as generation of proinflammatory cytokines that can cause direct tissue injury. Red cell exchange transfusion can be life-saving but the addition of therapeutic plasma exchange may further improve outcomes by removing such inflammatory mediators. Here, we describe the case of a 27-year-old male patient with sickle cell anaemia presenting with typical features of fat embolism syndrome including neurological involvement with greatly reduced level of consciousness. MRI of his brain showed multiple widespread microhemorrhages giving the characteristic "star field" pattern but also a cytotoxic lesion of the corpus callosum, known to be the result of direct neurotoxicity by proinflammatory cytokines. The patient underwent emergency red cell exchange transfusion leading only to modest clinical improvement but fully regained consciousness after three cycles of therapeutic plasma exchange. This case highlights the deleterious effect of the hyperinflammatory state characteristic of many sickle cell complications and supports further exploring the potential benefit from plasma exchange as an adjunct to red cell exchange in order to remove proinflammatory cytokines during acute complications of sickle cell disease.